2019
DOI: 10.1088/1757-899x/597/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Thermal protection of buildings from sandwich panels for Southern Siberia conditions

Abstract: Article represents recommendations on decrease in heat losses through heat-conducting inclusions of sandwich panels. Recommendations are based on the analysis of calculations by a finite element method in software package Elcut and thermal imaging. The purpose of this study is to increase the thermal protection of buildings built with sandwich panels for the South Siberia conditions. The way of decrease in the factor of cold bridges is studied by adding thermal insulation of panel node connections. The authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Based on the numerical analysis results, the regression equations for calculating minimal values of temperature on an internal surface of a vertical sandwich panel are easy to obtain. The analysis of the thermal field of the "sandwich panel -metal frame" [16][17][18] system shown that the hygiene requirements do not comply. The proposed solution allows the reduction of the influence of heat conducting inclusions on thermo-technical properties.…”
Section: Fig 1 Separation Of Bindings From Window Spansmentioning
confidence: 99%
“…Based on the numerical analysis results, the regression equations for calculating minimal values of temperature on an internal surface of a vertical sandwich panel are easy to obtain. The analysis of the thermal field of the "sandwich panel -metal frame" [16][17][18] system shown that the hygiene requirements do not comply. The proposed solution allows the reduction of the influence of heat conducting inclusions on thermo-technical properties.…”
Section: Fig 1 Separation Of Bindings From Window Spansmentioning
confidence: 99%